2008
DOI: 10.1159/000119702
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atorvastatin Treatment on Lipid Profile and Adhesion Molecule Levels in Hypercholesterolemic Patients: Relation to Low-Density Lipoprotein Receptor Gene Polymorphism

Abstract: Inflammation has been indicated to play a major role in the development of atherosclerosis. The beneficial effect of statins has been suggested to be related to their anti-inflammatory properties. We have studied plasma levels of soluble adhesion molecules in patients with hypercholesterolemia before and after 3 months of treatment with atorvastatin and evaluated possible relations to the mutations in low-density lipoprotein receptor (LDLR) gene. In patients with no LDLR gene polymorphism (group A), lower base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 70 publications
0
15
0
1
Order By: Relevance
“…CCL11, CCL13, CCL17, CCL22 and CCL26) levels in CD patients treated with atorvastatin. In addition, in our CD patient group atorvastatin shows no effect on adhesion molecules linked to leukocyte trafficking, such as E-selectin, P-selectin and ICAM-3, whereas in cardiovascular disease patients these adhesion molecules can be reduced by the statin therapy [35], [36], [37]. One can only speculate that the reason for these differences may reflect different effects of statins in relation to dosage, and co-treatments, and may reflect differences between the statin used, since all statins may not have the same therapeutic potential.…”
Section: Discussionmentioning
confidence: 61%
“…CCL11, CCL13, CCL17, CCL22 and CCL26) levels in CD patients treated with atorvastatin. In addition, in our CD patient group atorvastatin shows no effect on adhesion molecules linked to leukocyte trafficking, such as E-selectin, P-selectin and ICAM-3, whereas in cardiovascular disease patients these adhesion molecules can be reduced by the statin therapy [35], [36], [37]. One can only speculate that the reason for these differences may reflect different effects of statins in relation to dosage, and co-treatments, and may reflect differences between the statin used, since all statins may not have the same therapeutic potential.…”
Section: Discussionmentioning
confidence: 61%
“…This fact is in contradiction with some of the previous hypotheses that the expression of scavenger receptors is significantly increased especially during the evolution of monocytes to macrophages [ 20 ]. In patients with ACS up-regulated expression of investigated receptors in circulating monocytes can be strongly associated with the late stage of atherosclerosis, because the onset of acute symptoms is characterized by increased activity of monocytes and macrophages, as well as very high level of inflammation in the organism [ 4 , 21 , 39 ]. This hypothesis was confirmed in presented research through the analysis of the C-reactive protein concentration in plasma, which showed that in patients with acute coronary syndrome the level of CRP was even 100 fold higher than the accepted standards for healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidised lipoproteins (oxLDL) are the major factor responsible for the initiation and the acceleration of atherosclerosis. The processes activated by oxLDL are: endothelial dysfunction, expression of adhesion molecules, synthesis of chemoattractants and proinflammatory cytokines, or activation of monocytes and smooth muscle cells to migration into the area of inflammation [ 4 , 6 , 10 , 21 ]. Monocyte-derived macrophages are able to bind and accumulate of modified lipoproteins through the scavenger receptors-mediated endocytosis [ 14 16 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maron et al showed that statin treatment did not affect Lp(a) levels (25). These results may be explained by individual mutational differences, as indicated by Bolewski et al (26).…”
Section: Discussionmentioning
confidence: 95%